2019
DOI: 10.3384/diss.diva-156622
|View full text |Cite
|
Sign up to set email alerts
|

Health, obstetric outcomes and reproduction in women with vulvar pain or primary fear of childbirth

Abstract: Fear of childbirth (FOC) is common and affects approximately 5-20 % of all pregnant women. FOC is associated with giving birth by caesarean section on maternal request (CSMR). The rate of caesarean sections (CS) and CSMR has increased during the last decades. To decrease these women's fear, the rate of CSMR and to promote a more positive birth experience, many treatments for FOC have been evaluated. In Sweden, the treatment is individualized and given by obstetricians, midwives, psychologists or psychotherapis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 98 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Pregnant women who consulted an antenatal polyclinic at a related hospital between 01 May 2016 and 01 August 2016 were included in this study. To determine the sample size, a power analysis was conducted (sample error: 0.01 and power: 95%), and the prevalence of childbirth fear was estimated as 20%. The minimal number of people to be included in the study sample was calculated as 318.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women who consulted an antenatal polyclinic at a related hospital between 01 May 2016 and 01 August 2016 were included in this study. To determine the sample size, a power analysis was conducted (sample error: 0.01 and power: 95%), and the prevalence of childbirth fear was estimated as 20%. The minimal number of people to be included in the study sample was calculated as 318.…”
Section: Methodsmentioning
confidence: 99%
“…Severe FOC is an amount of worry that diminishes the woman's courage to have a baby or have a baby through vaginal delivery, or even it may result in a mental illness. Phobic FOC means that the fear is so much that the woman avoids becoming pregnant or vaginal childbirth, and sometimes it causes the woman to abort pregnancy . It has been reported that 20% of pregnant women are afraid of childbirth, including 10% of women who experience severe fear and 2.5% of women who experience fear at the phobic level …”
Section: Inroductionmentioning
confidence: 99%
“…The researchers created this form to collect information on some sociodemographic characteristics of the participants (e.g., age, education status, income status). 2,[4][5][6] Desire to Avoid Pregnancy (DAP) Scale DAP was developed by Rocca et al (2019) and tested for validity and reliability in Turkish by Karataş Okyay et al 5,7 It is a 14-item scale that measures the preferences, thoughts, and feelings of women regarding a future pregnancy and childbirth. Items 3, 7, 9, 11, 12, 13, and 14 are inversely scored, while items 1, 2, 4, 5, 6, 8, and 10 are directly scored.…”
Section: Personal Information Formmentioning
confidence: 99%
“…Tokophobia is the case where the fear experienced by the woman drives her towards avoiding pregnancy or childbirth or sometimes terminating her pregnancy. 2,3 While studies have focused on the fear of childbirth among pregnant women, less is known about the fear of childbirth among unmarried women. The prevalence of fear of childbirth was found among 13.6% of unmarried university students in Canada.…”
Section: Introductionmentioning
confidence: 99%